Simulating the Effects of Alternative Management Measures of Trawl Fisheries in the Central Mediterranean Sea: Application of a Multi-Species Bio-economic Modeling Approach - Russo, Tommaso; D'Andrea, Lorenzo; Franceschini, Simone; Accadia, Paolo; Cucco, Andrea; Garofalo, Germana; Gristina, Michele; Parisi, Antonio; Quattrocchi, Giovanni; Sabatella, Rosaria Felicita; Sinerchia, Matteo; Canu, Donata M.; et al. (Frontiers in Marine Science, 2019)
In the last decades, the Mediterranean Sea experienced an increasing trend of fish stocks in overfishing status. Therefore, management actions to achieve a more sustainable exploitation of fishery resources are required and compelling. In this study, a spatially-explicit multi-species bio-economic modelling approach, namely SMART, was applied to the case study of central Mediterranean Sea to assess the potential effects of different trawl fisheries management scenarios on the demersal resources. The approach combines multiple modelling components, integrating the best available sets of spatial data about catches and stocks, fishing footprint from VMS and economic parameters in order to describe the relationships between fishing effort pattern and impacts on resources and socio-economic consequences. Moreover, SMART takes into account the bi-directional connectivity between spawning and nurseries areas of target species, embedding the outcomes of a larvae transport Lagrangian model and of an empirical model of fish migration. Finally, population dynamics and trophic relationships are considered using a MICE (Models of Intermediate Complexity) approach. SMART simulates the fishing effort reallocation resulting from the introduction of different management scenarios. Specifically, SMART was applied to evaluate the potential benefits of different management approaches of the trawl fisheries targeting demersal stocks (deep-water rose shrimp P. longirostris, the giant red shrimp A. foliacea, the European hake M. merluccius and the red mullet M. barbatus) in the Strait of Sicily. The simulated management scenarios included both a reduction of the fishing capacity and effort, two different sets of temporal fishing closures and two sets of spatial fishing closures, defined involving fishers. Results showed that both temporal and spatial closures are expected to determine a significant improvement in the exploitation pattern for all the species, ultimately leading to the substantial recovery of spawning stock biomass for the stocks. Overall, one of the management scenario suggested by fishers scored better and confirms the usefulness of participatory approaches, suggesting the need for more public consultation when dealing with resource management at sea.